Independent Filmmaking in South East Asia : Conversations with Filmmakers on Building and Sustaining a Creative Career - Meissner, Nico, 1979- (Routledge, 2021)
Featuring interviews with 27 award-winning and emerging filmmakers, this book is the first comprehensive look at independent filmmaking careers in South East Asia with never-before published insights into the lives and careers of some of the most influential filmmakers in one of the world's most exciting screen production regions.Celebrating filmmaking in South East Asia, the interviews offer unique perspectives that highlight the various paths filmmakers have taken to establish and develop their independent filmmaking careers. Presenting filmmakers whose films span narrative, documentary and experimental genres, and from all ten South East Asian nations, the filmmakers in this collection include: Camera d'Or winner Anthony Chen Sundance Grand Jury Prize nominee Mouly Surya NETPAC Award Winner Sheron Dayoc Brunei's first female director, Siti Kamaluddin Directors of the Wathann Festival, Thaiddhiand Thu Thu Shein Lao's only female and first horror film director, Mattie Do Aimed at aspiring filmmakers with a focus on career building outside of global production hubs, Meiner has curated a collection of interviews that reflects the diversity and ambition of filmmaking in South East Asia. The book is accompanied by a companion website (www.southeastasianfilmcareers.com) that includes 27 micro-documentaries on the included filmmakers.
Acknowledgements; Introduction Chapter 1: Filmmaking in ... Brunei " Siti Kamaluddin; Chapter 2: Filmmaking in ... Cambodia " Morn Vanntey " Neang Kavich " Sokyou Chea; Chapter 3: Filmmaking in ... Indonesia " Juan Mayo " Mouly Surya " Nia Dinata; Chapter 4: Filmmaking in ... Laos " Anysay Keola " Mattie Do; Chapter 5: Filmmaking in ... Malaysia " Imri Nasution & Isazaly Isa " James Lee " Nandita Solomon; Chapter 6: Filmmaking in ... Myanmar " Hnin Ei Hlaing (Snow) " Thaiddhi & Thu Thu Shein " The Maw Naing; Chapter 7: Urban Sights - A Visual Essay; Chapter 8: Filmmaking in ... The Philippines " Hannah Espia " John Torres " Sheron Dayoc; Chapter 9: Filmmaking in ... Singapore " Anthony Chen " Daniel Yam " Sherman Ong; Chapter 10: Filmmaking in ... Thailand " Adam Yukol " Aditya Assarat " Anocha Suwichakornpong; Chapter 11: Filmmaking in ... Vietnam " Bui Kim Quy " Dao Thanh Hung & Pham Phuong Thao " Phan Dang Di; Index
OCLC-licensed vendor bibliographic record.
Keywords: Independent filmmakers -- Southeast Asia -- Interviews; Motion picture authorship -- Southeast Asia; PERFORMING ARTS / Film & Video / General